Autobiografia e Ficção: análise do narrador em Extinção - Uma Derrocada, de Thomas Bernhard - Santos, José Lucas Zaffani dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present dissertation aims to analyze the book Extinction - a collapse, of the Austrian writer Thomas Bernhard, published in 1986. The novel, related by Franz-Josef Murau, presents as a narrative situation the wish of this character to write his autobiography, as soon as he returns from Wolfsegg - where he attended his relatives' funeral - to Rome, where he lives since he left his family. However, in the end, after being announced the narrator's death, the same text can be read as the embodiment of his autobiographical project. Thus, this analysis starts from the constitution of the narrator-protagonist to reflect about his intention in writing his account, which has as the theme to deal with his homeland, Wolfsegg, in Austria. This research also aims to show the role of writing as a way of elaborating the traumatic past lived by the narrator beside his family, in Wolfsegg. This place reigns in the narrator's speech as absolute and, being the thematic core of his writing, it will also be analyzed to delineate the person who tells his story. It's necessary to discuss how this narrator selects and sorts the events which he describes because the novel is dominated by his view - in first person. These events intend to enhance the image that the protagonist wants to create of himself. In this novel, narrator and space categories seem to be only one and the writing designed by Murau must present the extinction of both

Esta dissertação tem como objetivo empreender uma análise da obra Extinção - Uma derrocada (Auslöschung - Ein Zerfall), publicado em 1986, pelo escritor austríaco Thomas Bernhard. O romance, narrado por Franz-Josef Murau, apresenta como situação narrativa o desejo desse personagem de escrever a sua autobiografia, tão logo retorne de Wolfsegg, onde fora participar do enterro de familiares, para Roma, onde vive desde que deixou a família. Entretanto, ao final do romance, após ser anunciada a morte do narrador, esse mesmo texto pode ser lido como a concretização de seu projeto autobiográfico. Desse modo, a presente análise parte da constituição do narrador-protagonista para refletir acerca de sua intenção ao escrever seu relato, o qual tem como tema abordar sua terra natal, Wolfsegg, na Áustria. Este trabalho visa mostrar também o papel da escrita como forma de elaboração do passado traumático vivido pelo narrador ao lado de sua família em Wolfsegg. Uma vez que esse espaço reina absoluto no discurso do narrador, sendo, portanto, o núcleo temático de sua escrita, ele também será analisado para que assim se possa melhor delinear o sujeito que conta a sua história. Devido ao fato de o romance ser dominado pelo campo de visão de um narrador em primeira pessoa, torna-se necessário abordar o modo como esse indivíduo seleciona e ordena os eventos que se põe a narrar, os quais visam a potencializar a imagem que o protagonista quer criar de si mesmo. Nesse romance, as instâncias do narrador e do espaço parecem ser um só e a escrita concebida por Murau deve apresentar a extinção de ambos
Keywords: Bernhard, Thomas 1931; Literatura; Narrativas pessoais; Subjetividade; Autobiografia; Espaço; Literature